2013
DOI: 10.1007/s12015-013-9452-5
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of malignancy by Smad3 in mouse embryonic stem cell formed teratoma

Abstract: Disease associated gene deficient embryonic stem cells can serve as valuable in vitro models to study disease mechanisms and screen drugs. Smad3 mediated TGF-β/Activin/Nodal signaling plays important roles in many biological processes. Despite numerous studies regarding Smad3 function, the role of Smad3 in mouse ES cells is not well studied. To understand the function of Smad3 in mouse ES cells, we derived Smad3-/- ES cells and wild type ES cells. Smad3-/- ES cells display no defect on self-renewal. They expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…It has also been documented that SMAD3 is the mediator of signals from the TGFβ superfamily, which controls cell proliferation, pluripotency, and differentiation [70]. Recently, it has been reported that SMAD3 is closely connected with teratoma formation from ESCs [71]. SMAD3 expression was down-regulated (Fig 7E and 7F).…”
Section: Discussionmentioning
confidence: 74%
“…It has also been documented that SMAD3 is the mediator of signals from the TGFβ superfamily, which controls cell proliferation, pluripotency, and differentiation [70]. Recently, it has been reported that SMAD3 is closely connected with teratoma formation from ESCs [71]. SMAD3 expression was down-regulated (Fig 7E and 7F).…”
Section: Discussionmentioning
confidence: 74%
“…A number of studies (Thomson et al, 1998;Wakitani et al, 2003;Stojkovic et al, 2005;Nussbaum et al, 2007;Dressel et al, 2008;Prokhorova et al, 2009;Zhang et al, 2012;Li et al, 2013;Lukovic et al, 2013) have shown the potential of ESCs to form teratomas by injecting undifferentiated ESCs into mice. Most studies used immunodeficient hosts such as severe combined immunodeficient (SCID) mice (Thomson et al, 1998;Wakitani et al, 2003;Stojkovic et al, 2005;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in many previous studies, the use of injected ESCs was associated with the risk of teratoma development (Wakitani et al, 2003;Baharvand and Matthaei, 2004;Przyborski, 2005;Nussbaum et al, 2007;Dressel et al, 2008;Prokhorova et al, 2009;Zhang et al, 2012;Li et al, 2013). In a clinical setting, this is a critical limitation of such a treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oct4‐GFP transgene male mice were crossed with C57‐BL/6 female mice and E3.5 blastocysts were harvested from the uterus of female mouse. The blastocysts were then seeded on mitomycin‐C inactivated MEF feeder in ES medium (Schoonjans et al, ; Hayashi et al, ; Li et al, , ). ICM outgrowth was formed 6 days later.…”
Section: Methodsmentioning
confidence: 99%